Inspirasi Kisah Ayub bagi Seorang Katolik dalam Menghadapi Penderitaan - Kurniadi, Bartholomeus Wahyu (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Job lives as a righteous man before God and he is one of the good models of believer. The Scripture tells about his experiences of severe and extreme sufferings. His wealth is lost, his children die, and he becomes painfully ill. His friends accuse him of being a sinner and they even avoid him. His wife tends to do the same as his friends do. Job is afflicted and lonely in his suffering. But Job responds to his suffering by an attitude of faith. Suffering is interpreted as a way to know and understand more his God. Suffering cannot be comprehended by interpretation, but should be responded by faith. Job walks through the mystery of suffering not merely with critical and rational thought, but eventually with a confession of faith, “I know that you can do all things” (Job 42:2a). But this is yet a ‘rational’ knowing that needs further decision in faith to accept every suffering as part of life in God. It is this decision to respond to suffering that makes the difference to the character of faith as experience, that is, the courage of being religious rather than simply of having a religion.